Students’ self-efficacy in mathematics academic achievement: Do teachers’ personality traits matter? - Emeda Tengaa, Peter (Edukasiana: Jurnal Inovasi Pendidikan, 2024)
Students' academic achievement is influenced by a wide range of factors, ranging from individual, family-related, school-related, and societal factors. The current study explores the effect of students’ self-efficacy (SSEF) on math academic achievement among secondary students, with a specific focus on the potential moderating role of teachers' personality traits (TPTS). To achieve the study objective, an epistemological-positivist research paradigm and cross-sectional research design were used to guide the study. Confirmatory factor analysis (CFA) and PROCESS macro were employed for data analysis. The results reveal a significant and positive correlation between SSEF beliefs and their math academic achievement (β = 0.4525, p = 0.0000). Moreover, the results demonstrate that the effect of SSEF on math academic achievement is significantly increasing at the increased level of TPTS (β = 0.0572, p = 0.0089), affirming the crucial role of TPTS in shaping SSEF and math academic endeavours. These findings hold relevant for educators, schools’ administrators, and policymakers. Among others, the study recommends the need to design and implement training programs, workshops, seminars and offer teaching tools that nurture and cultivate SSEF, self-esteem, and TPTS in shaping students' trajectories of math success. This study unravels the intricate interplay between self-efficacy, TPTS, and secondary students' achievements in the realm of mathematics. By so doing, the study contributes to both theoretical knowledge and practical insights, offering a deeper understanding of the complex factors influencing academic success in math among secondary students.